2010
DOI: 10.4218/etrij.10.0109.0447
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Bus Serialization Method for Low-Power Communications

Abstract: One of the critical issues in on‐chip serial communications is increased power consumption. In general, serial communications tend to dissipate more energy than parallel communications due to bit multiplexing. This paper proposes a low‐power bus serialization method. This encodes bus signals prior to serialization so that they are converted into signals that do not greatly increase in transition frequency when serialized. It significantly reduces the frequency by making the best use of word‐to‐word and bit‐by‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this paper, we proposed a lighting energy management system by using PC's power save mode as an occupancy sensing method. Although various energy management technologies have been developed in a chip and hardware level, we focused on an application level management to reduce the lighting energy management [10]- [13]. We described the correspondence between the lights and the PC's and explained the process mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we proposed a lighting energy management system by using PC's power save mode as an occupancy sensing method. Although various energy management technologies have been developed in a chip and hardware level, we focused on an application level management to reduce the lighting energy management [10]- [13]. We described the correspondence between the lights and the PC's and explained the process mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Bo decoding structures are placed at the ne before the serializer contrary to one on link CDBI [6] and SC [8] encoders operating on has also been implemented and mapped library. A comparison of area and powe illustrated in Fig 3.It can be observed that p (TSC) ensures minimum overhead in p (exception only in the case of BI encoder).…”
Section: B Logic Designmentioning
confidence: 99%
“…[8], [9] and [11] deal with reduction of switching activity in serial links (caused due to serialisation of parallel data). A few encoding techniques have been defined to take into consideration the contribution of crosscoupled capacitance [6], [12].…”
Section: Introductionmentioning
confidence: 99%
“…This means that double the wire costs are needed in asynchronous global signaling, and an increase in the number of wires among blocks can lead to a deterioration in design complexity and power consumption for an on-chip global interconnect. The bus serialization method [6] is one of solutions for this overhead.…”
Section: Introductionmentioning
confidence: 99%